A Simultaneous Equation Analysis Of The Relationship Between Foreign Direct Investment, Public Expenditure And Economic Growth In Nigeria - Ovenseri-Ogbom, O. Friday; Umoru, David (European Scientific Journal, ESJ, 2016)
The objective of the paper is to empirically examine the effect of FDI and public expenditure on the Nigerian economy. The simultaneous equation estimation was carried out in the study. From the elasticity-multiplier coefficient table, it became obvious that infrastructure measured by power generation is highly germane in stimulating economic growth and foreign direct investment. The study thus recommends the need for significant infrastructure such as power supply.